ANALISIS UMUR SIMPAN TEPUNG TERMODIFIKASI HASIL FERMENTASI UBI KAYU MENGGUNAKAN BAKTERI ASAM LAKTAT WIKAU MAOMBO - Herlina, Herlina (Journal of Applied Chemistry, 2017)
Modified cassava flour is one of the innovations of foodstuffs which had the potential tobe commercially produced. Therefore, the shelf life is an important factor that should be listed inthe product packaging. The purpose of this study was to give information to producers andconsumers or the general public about the shelf life of cassava flour modified products, so thatthe safety of the consumption of the product can be assured. Determination of the shelf life ofcassava flour modified using accelerated life testing (ASLT) with sorption isotherm curveapproach (critical moisture content). The method describes the addition or loss of the watercontent of food on constant of temperature and humidity (RH). The study was conducted with theinitial stages of the determination of moisture content, critical moisture content and equilibriummoisture content of the modified cassava (Manihot utilissima) and (Manihot esculenta Ctrantz)approximately 6.87%;6,24%, 6.92%; 6.31% and 10.30%; 8.45%, respectively. Sorption isothermcurve was selected Caurie equations model and permeability of polypropylene packaging used is0.0542 g/m2.day.mmHg. The results showed that the shelf life modified cassava (Manihotutilissima) and (Manihot esculenta Ctrantz) are 1 year 4 month and 1 year 8 month.